2008
DOI: 10.1016/s1008-1275(08)60063-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypogastric artery autograft treating hemorrhage with infection of external iliac artery secondary to renal transplantation

Abstract: Massive hemorrhage from infected anastomosed site between the graft artery and the external iliac artery is one of the most serious complications of renal transplantation. Clinically, it is a rare but fatal occasion. We reported here one case of hemorrhage with infection in the iliac artery anastomosed site treated successfully with hypogastric artery autograft interposition in March 2003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…interposition grafts were successfully used to repair the defects formed in the EIA resulting from the excision of infected aneurysms. Wang et al17 reported the use of IIA graft in treating a patient with massive hemorrhage as a result of bacterial contamination of the anastomosed site between the graft artery and the EIA. Lacombe et al 18 reported the use of IIA graft in the repair of a mycotic aneurysm of the EIA secondary to bacteremia.…”
mentioning
confidence: 99%
“…interposition grafts were successfully used to repair the defects formed in the EIA resulting from the excision of infected aneurysms. Wang et al17 reported the use of IIA graft in treating a patient with massive hemorrhage as a result of bacterial contamination of the anastomosed site between the graft artery and the EIA. Lacombe et al 18 reported the use of IIA graft in the repair of a mycotic aneurysm of the EIA secondary to bacteremia.…”
mentioning
confidence: 99%